2009
DOI: 10.1002/cbic.200900451
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electrostatic Shielding on H Tunneling in R67 Dihydrofolate Reductase

Abstract: The nature of the CH→C transfer catalyzed by the primitive plasmidal enzyme R67 dihydrofolate reductase was examined as function of the ionic strength of the medium. Kinetic isotope effects and theoretical calculations suggested that, at high ionic strength, electrostatic repulsion between the H donor and H acceptor is reduced, and the reaction coordinate is better organized for H tunneling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The quantum corrected ratios of phenomenological rates were computed, and using these ratios, H/D KIEs are plotted in Figure 1C. The temperaturedependent KIEs for R67 DHFR in this work are in good agreement with the experimentally obtained trend 87,88 although the values are slightly underestimated from the calculations (Figure 1D). As a comparison, we also compute the gas-phase KIEs within the standard harmonic approximation (no tunneling correction) for the hydride transfer between the reacting fragments CH 3 -H 2 nic and 6-CH 3 -H 3 pterin + .…”
Section: ■ Results and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The quantum corrected ratios of phenomenological rates were computed, and using these ratios, H/D KIEs are plotted in Figure 1C. The temperaturedependent KIEs for R67 DHFR in this work are in good agreement with the experimentally obtained trend 87,88 although the values are slightly underestimated from the calculations (Figure 1D). As a comparison, we also compute the gas-phase KIEs within the standard harmonic approximation (no tunneling correction) for the hydride transfer between the reacting fragments CH 3 -H 2 nic and 6-CH 3 -H 3 pterin + .…”
Section: ■ Results and Discussionsupporting
confidence: 79%
“…Experimental studies on the primitive R67 DHFR revealed temperature-dependent KIEs. These studies suggested that the primitive enzyme is poorly preorganized and requires significant gating of its DAD prior to the reaction, resulting in significant temperature dependence. , The advantage of studying R67 DHFR is its simple kinetic scheme, with measured KIEs that are nearly free of kinetic complexity.…”
Section: Introductionmentioning
confidence: 99%
“…In the earlier paper [24] reported is an enhancement in the rate of hydride transfer in a plasmid encoded dihydrofolate reductase R67 DHFR with increasing ionic strength. The findings are explained [25] in terms of effect of electrostatic shielding on hydrogen tunneling in the R67 dihydrofolate reductase where, at higher ionic strength, the donor and acceptor of the hydride were better oriented for hydrogen tunneling than the same system at lower ionic strength. To the best of our knowledge, there is no report on the issue related to solution chemistry.…”
mentioning
confidence: 83%
“…The question could be of relevance for other systems, among others the PCET systems in protein environment. There are only few reports on the matter related to an enzyme system [24] [25]. In the earlier paper [24] reported is an enhancement in the rate of hydride transfer in a plasmid encoded dihydrofolate reductase R67 DHFR with increasing ionic strength.…”
mentioning
confidence: 97%
“…129 A primitive, bacterial plasmid encoded DHFR has been characterized 132 and shows temperature-dependent kinetic isotope effects, consistent with the idea that the temperature-independent kinetic isotope effects seen in native enzymes are characteristic of highly evolved enzymes. 133,134 …”
Section: Dihydrofolate Reductasesmentioning
confidence: 99%